Undang-undang kepailitan dan penundaan kewajiban pembayaran utang (UU RI No.37 Th.2004) - [Tidak Terdaftar] (Sinar Grafika, 2006)
Undang-undang kepailitan dan penundaan kewajiban pembayaran utang (UU RI No.37...